Accuracy-optimal algorithm for solution of one problem of numerical integration - Zadiraka , V. K.; Abatov , N. T. (Ukrains’kyi Matematychnyi Zhurnal, 1991)
We study optimally exact algorithms for calculation of integrals of certain quickly oscillating functions. We construct an optimally exact passive algorithm for a class of functions with a known number of extrema.